Retroregulation of the bacteriophage lambda int gene: limited secondary degradation of the RNase III-processed transcript. - Plunkett, G (1989)
Expression of the int gene of bacteriophage lambda from two promoters, pI and pL, is differentially regulated through RNA processing. Efficient Int protein synthesis from the pL RNA is inhibited by the action of sib, a cis-acting retroregulator downstream from the int gene. We have used mapping procedures with nuclease S1 to study the pL transcripts produced in vivo after phage lambda infection. We have found an RNase III-dependent processing site within the Int coding sequence, 387 nucleotides upstream from the site of the primary cleavage by RNase III at Sib. This secondary processing site is located at the most stable region of secondary structure in the sib int region, as predicted by computer analysis. We suggest that RNase III cleavage at the Sib site allows processive exonucleolytic degradation of the RNA to proceed to a region of secondary structure within the Int coding sequence, which protects the upstream region of the transcript from further degradation.